Real estate investment funds in Poland - Śmiałek Michał (My University, 2008)
The thesis has two objectives. The first one is to present the real estate investment funds market in Poland, along with legal foundations on which it was built. The other one is to asses real estate investment funds from the point of view of potential investors. This includes assessment of efficiency of real estate funds alone, as well as usefulness of these funds for improving performance of a portfolio of investments. The author of the thesis is asking the following questions: Is diversification a mere marketing catch of the real estate investment funds industry, or are there facts to support such opinions? Can investors benefit from including real estate funds in their portfolios? As a first step to address these questions, the author investigates what are the foundations of the real estate investment funds market in Poland. After the foundations of the market have been explained, the market itself is researched. Funds operating in Poland are categorized and differences between them are explained and quantitative analysis of real estate investment funds are performed.
Fundusze inwestycyjne rynku nieruchomości w Polsce
Keywords: real estate market; investment funds; closed-end real estate funds; open-end real estate funds; investment decisions